2009
DOI: 10.1590/s1413-41522009000200009
|View full text |Cite
|
Sign up to set email alerts
|

Modelação matemática e otimização operacional de processos de membrana de ultrafiltração

Abstract: A utilização de processos de membrana em Engenharia Ambiental tem expandido de forma significativa nos últimos anos e, tendo em vista a importância da possibilidade de otimização da sua operação com vistas à produção máxima de permeado em função do tempo, este trabalho teve por objetivo definir uma técnica de otimização da operação de sistemas de ultrafiltração mediante o estudo de ciclos de operação e lavagem. Os ensaios experimentais foram efetuados tendo-se empregado duas membranas de ultrafiltração com dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
6
0
2
Order By: Relevance
“…One of the worst problems cited by the authors during the operation of membrane systems is the decay of the flow over time. This phenomenon is called "fouling" or "membrane fouling" [27][28][29][30][31].…”
Section: Operation Of Membrane Separation Processes and Factors Influmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the worst problems cited by the authors during the operation of membrane systems is the decay of the flow over time. This phenomenon is called "fouling" or "membrane fouling" [27][28][29][30][31].…”
Section: Operation Of Membrane Separation Processes and Factors Influmentioning
confidence: 99%
“…That is, the solute is concentrated in the region close to the membrane/solution interface, preventing the passage of the solvent. According to the authors [27], the reduction in the permeate flux during the filtration, applying constant pressure, occurs due to the deposition of colloidal particles and macromolecules on the surface of the membrane. Thus, the authors state that membrane cleaning should be performed periodically during the operation of the system to prevent the possibility of extreme membrane fouling and even irreversible fouling.…”
Section: Operation Of Membrane Separation Processes and Factors Influmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been reported in the literature using ceramic membranes as device to separate water/oil mixture [8][9][10][11] and have shown a separation efficiency ranging between 95% to 99.9% depending on the membrane and of the fluids properties that you want to separate. However, these devices have shown a deficiency with respect to the permeate flow that is reduced over time due to fouling pores.…”
Section: Introductionmentioning
confidence: 99%